Upregulating the Expression of LncRNA ANRIL Promotes Osteogenesis via the miR-7-5p/IGF-1R Axis in the Inflamed Periodontal Ligament Stem Cells - Bian, Minxia; Yu, Yan; Li, Yuzhi; Zhou, Zhou; Wu, Xiao; Ye, Xiaying; Yu, Jinhua (Frontiers in Cell and Developmental Biology, 2021)
Background: Long non-coding RNA (lncRNA) antisense non-coding RNA in the INK4 locus (ANRIL) is a base length of about 3.8kb lncRNA, which plays an important role in several biological functions including cell proliferation, migration, and senescence. This study ascertained the role of lncRNA ANRIL in the senescence and osteogenic differentiation of inflamed periodontal ligament stem cells (iPDLSCs). Methods: Healthy periodontal ligament stem cells (hPDLSCs) and iPDLSCs were isolated from healthy/inflamed periodontal ligament tissues, respectively. The proliferation abilities were determined by CCK-8, EdU assay, and flow cytometry (FCM). The methods of western blot assay (WB), quantitative real-time polymerase chain reaction (qRT-PCR), alizarin red staining, Alkaline phosphatase (ALP) staining, ALP activity detection, and immunofluorescence staining were described to determine the biological influences of lncRNA ANRIL on iPDLSCs. Senescence-associated (SA)-β-galactosidase (gal) staining，Western blot analysis, and qRT-PCR were performed to determine cell senescence. Dual-luciferase reporter assays were conducted to confirm the binding of lncRNA ANRIL and miR-7-5-p, as well as miR-7-5p and insulin-like growth factor receptor (IGF-1R). Results: HPDLSCs and iPDLSCs were isolated and cultured successfully. LncRNA ANRIL and IGF-1R were declined while miR-7-5p was upregulated in iPDLSCs compared with hPDLSCs. Overexpression of ANRIL enhanced the osteogenic protein expressions of OSX, RUNX2, ALP, and knockdown the aging protein expressions of p16, p21, p53. LncRNA ANRIL could promote the committed differentiation of iPDLSCs by sponging miR-7-5p. Upregulating miR-7-5p inhibited the osteogenic differentiation of iPDLSCs. Further analysis identified IGF-1R as a direct target of miR-7-5p. The direct binding of lncRNA ANRIL and miR-7-5p, miR-7-5p and the 3’-UTR of IGF-1R were verified by dual-luciferase reporter assay. Besides, rescue experiments showed that knockdown of miR-7-5p reversed the inhibitory effect of lncRNA ANRIL deficiency on osteogenesis of iPDLSCs. Conclusion: This study disclosed that lncRNA ANRIL promotes osteogenic differentiation of iPDLSCs by regulating the miR-7-5p/IGF-1R axis.